2020
DOI: 10.1136/bcr-2020-234651
|View full text |Cite
|
Sign up to set email alerts
|

Near-fatal negative pressure pulmonary oedema successfully treated with venovenous extracorporeal membrane oxygenation performed in the hybrid emergency room

Abstract: We report a rare case of negative pressure pulmonary oedema (NPPE), a life-threatening complication of tracheal intubation. A 41-year-old obese man was admitted to a previous hospital for neck surgery. After extubation, he developed respiratory distress followed by haemoptysis and desaturation. The patient was reintubated and brought to our hospital where we introduced venovenous extracorporeal membrane oxygenation (ECMO) to prevent cardiac arrest, which is an unusual clinical course for NPPE. He returned to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…The cannulae can be immediately and safely positioned with use of moveable C-arm fluoroscopy and ultrasonography equipment soon after early CT examination. As some researchers have reported, [17][18][19][20] initiation of VA or VV ECMO in the hybrid ER could be a safe and highly effective treatment to rescue severely injured or ill patients.…”
Section: Evidence For the Benefits Of The Hybrid Er In Various Fields...mentioning
confidence: 99%
See 1 more Smart Citation
“…The cannulae can be immediately and safely positioned with use of moveable C-arm fluoroscopy and ultrasonography equipment soon after early CT examination. As some researchers have reported, [17][18][19][20] initiation of VA or VV ECMO in the hybrid ER could be a safe and highly effective treatment to rescue severely injured or ill patients.…”
Section: Evidence For the Benefits Of The Hybrid Er In Various Fields...mentioning
confidence: 99%
“…Among patients with severe illness, Matsumura et al reported a rare case of negative pressure pulmonary edema, which is a potentially life‐threatening complication of general anesthesia with tracheal intubation. Because the patient could not be optimally managed with mechanical ventilation, VV ECMO could be started within 18 min of the patient's arrival in the hybrid ER without complications, and cardiopulmonary arrest was prevented 19 . In patients with massive pulmonary embolism (PE) requiring extracorporeal cardiopulmonary resuscitation (ECPR), safe and prompt initiation of VA ECMO is essential.…”
Section: Establishment Of a Hybrid Ermentioning
confidence: 99%
“…One recent study reported an incidence of 21.6% in patients with a lung collapse duration longer than 4 days and severe lung collapse. The acute clinical course of REPE resembles that of negative pressure pulmonary oedema, another possible aetiology of non-cardiogenic pulmonary oedema, which may also occasionally require VV-ECMO therapy 3. The recommended clinical management is supportive care consisting of non-invasive positive-pressure ventilation, as well as mechanical ventilation, if necessary.…”
Section: Descriptionmentioning
confidence: 99%
“…Conventional treatment of severe NPPE is focused on relieving the upper airway obstruction, positive pressure ventilation, and medication therapy including diuretics, with resolution of most cases. Case reports have described the need for delayed veno-venous extracorporeal membrane oxygenation (VV ECMO) in cases of refractory hypoxia not responding to initial therapies 2,3,4,5 . However, the use of VV ECMO as acute rescue therapy in the post anesthesia care unit (PACU) for NPPE-induced severe hypoxic respiratory failure, shock, and peri-arrest physiology is yet to be described in the literature.…”
Section: Introductionmentioning
confidence: 99%